COVID-19 Collaborations Researching Poverty and Low-Income Family Life during the Pandemic - Garthwaite, Kayleigh; Patrick, Ruth; Power, Maddy; Tarrant, Anna; Warnock, Rosalie (Policy Press, 2022)
Epdf and ePUB available Open Access under CC BY NC ND licence. This book presents the collaborative process of 14 research projects working together during the COVID-19 pandemic. It documents their findings and explains how researchers in the voluntary sector and academia responded methodologically, practically, and ethically to researching poverty and everyday life for families on low incomes during the pandemic.